From Financial Literacy to Financial Behavior: The Mediating Role of Behavioral Intention Among Generation Z University Students - Rita Kusumawati; Nabilah Cahya Ningrum (SENTRALISASI, 2026)
This study aims to analyze the effect of financial literacy and financial attitudes on financial behavior, mediated by behavioral intentions, among Management students at Muhammadiyah University Yogyakarta. The subjects in this study were active students enrolled in the Management program at Muhammadiyah University Yogyakarta. In this study, the sample consisted of 340 respondents selected through purposive sampling. The analysis tool used was SmartPLS 4.1.1.4 software. Based on the analysis, it was found that financial literacy and financial attitudes had a positive and significant effect on financial behavior. Behavioral intention significantly mediated the effect of financial literacy and financial attitudes on financial behavior.